(untitled) (Bangladesh Journal of Pharmacology, 2019)
Hydrogen sulfide has been shown to protect myocardium against ischemia-reperfusion injury by preserving interfibrillar mitochondria functional activities than subsarcolemmal mitochondria. In this study, the role of the KATP channel in modulating the mitochondrial subpopulations during the cardioprotection mediated by NaSH (H2S donor) was investigated. Isolated rat hearts were treated with mitochondrial KATP channel closer glibenclamide (10 μM)/opener diazoxide (0.8 mM) via Langendorff perfusion apparatus before ischemia-reperfusion. The results showed that NaSH pre-conditioning in presence of glibenclamide significantly improved cardiac recovery without any significant difference between interfibrillar mitochondria and subsarcolemmal mitochondria. In conclusion, targeting KATP channel may not be good option to target interfibrillar mitochondria/subsarcolemmal mitochondria against ischemia-reperfusion injury. Video Clip of Methodology: Langendorff isolated rat heart experiment: 4 min 44 sec: Click to watch